Secure network coding scheme for scalable video streaming - Xi-meng LIU; Guang-jun LIU; Jian-feng MA; Jin-bo XIONG (Tongxin xuebao)
With the purpose to achieve hierarchical security levels for scalable video streaming in heterogeneous net-works,random function was used to randomize parts of the video streaming in each layer.Network coding scheme was also used to resist known-plaintext attacks.Moreover,network encoder was studied.Ordered random linear network en-coder was designed for scalable video transmission.It could achieve scalability in security levels with few random opera-tions and reduce communication overhead.Analysis shows that the scheme could effectively increase the network throughput.